(untitled) (Revista Apotheke, 2022)
This article seeks to consider the visual arts internship as a field of research, as a contact between plastic investigation and teaching in the formation of the art teacher. This connection between research and education can enable collaborative experiences that break with the disciplinary model that operates in most schools. In light of Foucault’s ideas (2019), the internship and the school are seen as objects of research, in the search to develop strategies, beyond the school exercises of transmitting information (PEY, 2000). The artistic making implies movements in space and actions that contrast with the immobilization of the body in school’s desks and in front of screens. The internship can make room for an education that does not trigger disciplining devices, but leaves indifference behind in order to problematize a pedagogy divided into leaders and directed, which has the hierarchical norm as a policy of truth.